Impulse Noise Mitigation by Time-Diversity Hermitian Symmetry in Hybrid Powerline and Visible Light Communication Systems - Mulundumina Shimaponda-Nawa; Oluwafemi Kolade; Jianhua He; Wenbo Ding; Ling Cheng (IEEE Access)
Hybrid powerline and visible light communication (HPV) systems offer a cost-effective method of providing high-speed communication in indoor and outdoor environments, for the realisation of internet of things (IoT). However, in the HPV system the powerline communication (PLC) channel is inherently susceptible to impulse noise (IN) due to electrical appliances randomly connected to the powerline. This adversely affects the HPV system’s bit error rate (BER) performance. In this paper, a time-diversity Hermitian symmetry (TDHS) scheme, which mitigates the effects of IN in a PLC channel is proposed. The scheme employs the Hermitian symmetry structure to recover information symbols likely to have been affected by the IN. By using the TDHS scheme, the probability of the effect of IN on data symbols through a PLC channel, is drastically reduced by 75%. By simulations, the effectiveness of the TDHS scheme is demonstrated via the enhanced BER performance of the system. The TDHS scheme is then implemented over a permutation coded HPV system using the amplify-and-forward protocol at the PLC-VLC integration unit and the Hungarian-Murty (HM) soft-decision decoder at the destination. The combination of the TDHS scheme and the HM decoder in a coded system provides further BER performance enhancement, exceeding 10 dB gain in signal-to-noise ratio (SNR) at a BER of $10^{-4}$ .